Application of multimodal analgesia combined with opioid-free anesthetics in a non-intubated video-assisted thoracoscopic surgery bullectomy: A case report - Zheng, Longbin; Zhang, Xiaojing; Ma, Qing; Qin, Weimin; Liang, Wenbo; Ren, Zhiqiang; Fan, Guoxiang; Yin, Ning (Frontiers in Surgery, 2023)
Background Non-intubated video-assisted thoracoscopic surgery (NIVATS) has been increasingly applied worldwide owing to its benefits of enhanced recovery after surgery (ERAS). Anesthetic management for patients with asthma should focus on minimizing airway stimulation. Case description A 23-year-old male patient with a history of asthma was diagnosed with left-sided spontaneous pneumothorax. The patient then underwent left-sided NIVATS bullectomy under general anesthesia with preserved spontaneous breathing. Left thoracic paravertebral nerve block (TPVB) with an injection of 0.375% ropivacaine (30 ml) was performed in the 6th paravertebral space under ultrasound guidance. Anesthesia induction commenced until the cold sensation in the surgical area had disappeared. General anesthesia was induced by midazolam, penehyclidine hydrochloride, esketamine, and propofol and then maintained using propofol and esketamine. Surgery commenced after the patient was positioned in the right lateral recumbency. The collapse of the left lung was satisfactory, and the operative field was ensured after artificial pneumothorax. The surgical procedure was uneventful, intraoperative arterial blood gases were within normal ranges, and vital signs were stable. The patient awakened rapidly without any adverse reactions at the end of the surgery and was then transferred to the ward. During the postoperative follow-up, the patient experienced mild pain 48 h after surgery. The patient was discharged from the hospital 2 days postoperatively and developed no nausea, vomiting, or any other complications. Conclusion The present case suggests the feasibility of TPVB in combination with non-opioid anesthetics to provide high-quality anesthesia in patients undergoing NIVATS bullectomy.